Characteristics and feasibility of olive oil-based diacylglycerol plastic fat for use in compound chocolate - Chen, Ying; Wang, Weifei; Zhang, Weiqian; Tan, Chin-Ping; Lan, Dongming; Wang, Yonghua (Elsevier, 2022)
With an aim to prepare the healthier functional chocolate, olive oil-based diacylglycerol plastic fat (ODAGP) was prepared by mixing olive oil-based diacylglycerol stearin (O-DAGS) and olive oil-based diacylglycerol olein (O-DAGO) as confectionery fat in compound chocolate. We reported the physicochemical properties of ODAGP and ODAGP-CB blends, and then evaluated their application potential in compound chocolate based on sensory, blooming property and polymorphic transition. ODAGP (40% O-DAGS) showed a wide plastic range (7.1–45.2%) and high component compatibility. The crystal properties results indicated that ODAGP mainly existed in stable β-forms (β1 and β2). On the other hand, the ODAGP-CB binary system containing 10–40% ODAGP displayed similar melt-in-mouth property and crystal polymorphism (Form V) to natural CB. Compound chocolate prepared with ODAGP-CB blends obtained satisfactory overall acceptability (score > 7.8) and showed stronger fat bloom resistance.